Using Mesenchymal Stem Cells to Treat Female Infertility: An Update on Female Reproductive Diseases. (6th December 2019) - Zhao, Yun-xia; Chen, Shao-rong; Su, Ping-ping; Huang, Feng-huang; Shi, Yan-chuan; Shi, Qi-yang; Lin, Shu
Abstract : Female infertility impacts the quality of life and well-being of affected individuals and couples. Female reproductive diseases, such as primary ovarian insufficiency, polycystic ovary syndrome, endometriosis, fallopian tube obstruction, and Asherman syndrome, can induce infertility. In recent years, translational medicine has developed rapidly, and clinical researchers are focusing on the treatment of female infertility using novel approaches. Owing to the advantages of convenient samples, abundant sources, and avoidable ethical issues, mesenchymal stem cells (MSCs) can be applied widely in the clinic. This paper reviews recent advances in using four types of MSCs, bone marrow stromal cells, adipose-derived stem cells, menstrual blood mesenchymal stem cells, and umbilical cord mesenchymal stem cells. Each of these have been used for the treatment of ovarian and uterine diseases, and provide new approaches for the treatment of female infertility.